2014
DOI: 10.1039/c4cp01982b
|View full text |Cite
|
Sign up to set email alerts
|

Gas-surface reactions of nitrate radicals with vinyl-terminated self-assembled monolayers

Abstract: Interfacial reactions between gas-phase nitrate radicals, a key nighttime atmospheric oxidant, and a model unsaturated organic surface have been investigated to determine the reaction kinetics and probable reaction mechanism. The experimental approach employs in situ reflection-absorption infrared spectroscopy (RAIRS) to monitor bond rupture and formation while a well-characterized effusive flux of NO3 impinges on the organic surface. Model surfaces are created by the spontaneous adsorption of vinyl-terminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 69 publications
2
18
1
Order By: Relevance
“…For the unsaturated molecules studied we obtained rate coefficients on the order of 10 −8 cm 2 molecule −1 s −1 , which leads to uptake coefficients, γ , for NO 3 on a droplet covered in a monolayer of organic compound to be on the order of 10 −3 . These results broadly agree with the very limited number of measurements found in the literature (Moise et al, 2002;Knopf et al, 2006;Xiao and Bertram, 2011;Zhao et al, 2011;Zhang et al, 2014b) for unsaturated organics exposed to NO 3 in particular when considering that experiments are often carried out in very different conditions (e.g. on a gold surface instead of the water surface we used) and employ fundamentally different experimental approaches (e.g.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For the unsaturated molecules studied we obtained rate coefficients on the order of 10 −8 cm 2 molecule −1 s −1 , which leads to uptake coefficients, γ , for NO 3 on a droplet covered in a monolayer of organic compound to be on the order of 10 −3 . These results broadly agree with the very limited number of measurements found in the literature (Moise et al, 2002;Knopf et al, 2006;Xiao and Bertram, 2011;Zhao et al, 2011;Zhang et al, 2014b) for unsaturated organics exposed to NO 3 in particular when considering that experiments are often carried out in very different conditions (e.g. on a gold surface instead of the water surface we used) and employ fundamentally different experimental approaches (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…They suggested that a possible reason for this higher value compared to the results of Moise et al (2002) is the location of the double bond at the interface. Zhang et al (2014b) determined the uptake coefficient of NO 3 on a model surface of a self-assembled monolayer of vinyl-terminated alkanethiols on gold substrate to be (2.3 ± 0.5) × 10 −3 , monitoring the double bond rupture. The present results for organic monolayers at the air-water interface are in a better agreement with those of Moise et al (2002) and Zhang et al (2014b).…”
Section: Discussionmentioning
confidence: 99%
“…that are always present in such ambient pressure studies. An interesting comparison to the current study is the recent UHV-based experiments reported by Zhang et al 30 The initial reaction probability they reported for reactions of NO 3 with an 18-C vinylterminated SAM is about a factor of 3 smaller than the value reported here. The factor-of-three greater reactivity for the HO-SAM may be related to the greater accessibility of the reaction site (the α-H) caused by hydrogen bonding among terminal groups.…”
Section: Resultscontrasting
confidence: 63%
“…Reproduced from ref. 115 with permission from the PCCP Owner Societies. systems to better model heterogeneous atmospheric chemistry by including highly defective surfaces and the presence of critical co-reactants within the surfaces as well as within the gas phase.…”
mentioning
confidence: 99%
“…In an effort to explore the interfacial chemistry of nitrate radicals at organic surfaces in the absence of background gases and other possible contaminants, Zhang et al 115 explored these reactions at the surface of an alkenethiol self-assembled monolayer in the highly regulated environment of a UHV chamber. Additionally, the use of in situ reflection-absorption infrared spectroscopy (RAIRS) in their work allowed for the characterization of the surface during the course of nitrate radical exposure, thereby enabling an in-depth study of the reaction kinetics.…”
mentioning
confidence: 99%